The Lingual Unit of Batak Simalungun Traditional Wedding Ceremony in The Medan of Etnolinguistic Study - Rehulina, Rehulina; Rokhman, Fathur; Mardikantoro, Hari Bakti (Pascasarjana Universitas Negeri Semarang)
The purpose of this study were provided and explained the forms of lingual units and the meaning of lingual units contained in the Batak Simalungun traditional wedding ceremony in Medan. The data in this qualitative study were obtained using the method of listening and proficiency. The data analysis is used in the matching and distribution method with techniques for direct elements. The data analysis was carried out through two procedures, namely analysis during data collection and analysis after data collection. The results obtained are as follows. First, lingual unit forms include words, phrases, sentences, and speech. The lingual unit in the form of a word includes the word monomorfemis and the polymorphemic word form. Second, the cultural meaning of the lingual unit which includes (1) the meaning of human relations with God, (2) the meaning of human relations with the humans, and (3) the meaning of married life